2016
DOI: 10.1523/jneurosci.0945-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Signaling Promotes Vestibular Compensation by Increasing Neurogenesis and Remodeling the Expression of Potassium-Chloride Cotransporter KCC2 and GABAAReceptor in the Vestibular Nuclei

Abstract: Reactive cell proliferation occurs rapidly in the cat vestibular nuclei (VN) after unilateral vestibular neurectomy (UVN) and has been reported to facilitate the recovery of posturo-locomotor functions. Interestingly, whereas animals experience impairments for several weeks, extraordinary plasticity mechanisms take place in the local microenvironment of the VN: newborn cells survive and acquire different phenotypes, such as microglia, astrocytes, or GABAergic neurons, whereas animals eventually recover complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(130 citation statements)
references
References 75 publications
6
111
0
13
Order By: Relevance
“…Furthermore, compared with the RIH þ DMSO group, the expression of total KCC2, KCC2 oligomer, monomer, and oligomer/ monomer ratios were upregulated in the RIH þ PNU group, but KCC2 oligomer and monomer expression was still lower than in sham-operated groups (P < 0.05) (Figure 7(i) to (l)). Time courses of protein expression of total KCC2, KCC2 oligomer and monomer, and oligomer/monomer ratios in the spinal dorsal horn showed that those of the RIH þ PNU group returned to baseline levels on postoperative day 7, which is significantly earlier than in the RIH þ DMSO group (postoperative day 14), approximately correlating with nociceptive behavior (P < 0.05) (Figure 8(c) to (g)). We also studied the effects of PNU-120596 on KCC2 expression in the spinal dorsal horn by immunoFuorescence assay.…”
Section: The Time Course Of the Effects Of Pnu-120596 On The Expressimentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, compared with the RIH þ DMSO group, the expression of total KCC2, KCC2 oligomer, monomer, and oligomer/ monomer ratios were upregulated in the RIH þ PNU group, but KCC2 oligomer and monomer expression was still lower than in sham-operated groups (P < 0.05) (Figure 7(i) to (l)). Time courses of protein expression of total KCC2, KCC2 oligomer and monomer, and oligomer/monomer ratios in the spinal dorsal horn showed that those of the RIH þ PNU group returned to baseline levels on postoperative day 7, which is significantly earlier than in the RIH þ DMSO group (postoperative day 14), approximately correlating with nociceptive behavior (P < 0.05) (Figure 8(c) to (g)). We also studied the effects of PNU-120596 on KCC2 expression in the spinal dorsal horn by immunoFuorescence assay.…”
Section: The Time Course Of the Effects Of Pnu-120596 On The Expressimentioning
confidence: 92%
“…The cotransporter K þ -Cl À cotransporter-2 (KCC2) plays a critical role in maintaining low Cl À concentration inside neurons of the central nervous system (CNS), and it is indispensable for postsynaptic inhibition caused by GABA. It has been reported that GABAergic disinhibition is caused by the activation of spinal brain-derived neurotrophic factor/ tyrosine receptor kinase B-K þ -Cl À cotransporter-2 (BDNF/trkB-KCC2) signal, 9,11,[14][15][16] which is the underlying mechanism of morphine-induced hyperalgesia and formalin-induced pain at the spinal level. 11,17 Upregulation of spinal microglia BDNF promotes the decrease in KCC2 protein expression and transport activity on the surface of neurons, which results in hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although early depolarizing GABA A R signaling promotes neuronal maturation (Ben‐Ari et al, ), growing evidence suggests that BDNF signaling can promote transient excitatory (or diminished inhibitory) GABA A R signaling following noxious stimuli or injury. Adult cats who receive BNDF treatment following a unilateral vestibular neurectomy, a procedure reported to enhance reactive cell proliferation in the vestibular nucleus and recovery following CNS injury (Tighilet et al, ), demonstrate accelerated functional recovery associated with decreased KCC2 and increased GABA A R levels (Dutheil et al, ). A BDNF/TrkB‐dependent depolarizing shift in E GABA also occurs pre‐synaptically following nerve injury in the spinal cord that reduces presynaptic inhibition and contributes to the initiation of neuropathic pain (Chen et al, ).…”
Section: Neuropeptide and Neurosteroid Modulationmentioning
confidence: 99%
“…BDNF deficiency causes severe loss and degeneration of vestibular neurons, and contributes to vestibular dysfunction (10,11). A previous study demonstrated that the upregulation of BDNF accelerates the process of vestibular compensation (7). Therefore, BDNF appears to be important in vestibular compensation.…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) regulates synaptic transmission and plasticity (6), contributes to neurogenesis (7), and is involved in spatial orientation (8), motor and cognitive skills (9); thus, it has been closely associated with the development of the vestibular system. BDNF, an activity-dependent release substance, functions through binding to its affinity receptor tyrosine receptor kinase B (TrkB) in the vestibular system (5).…”
Section: Introductionmentioning
confidence: 99%